A copula-based method for synthetic microarray data generation - Lew, Sergio (2012)
In this work, we propose a copula-based method to generate synthetic gene expression data that account for marginal and joint probability distributions features captured from real data. Our method allows us to implant significant genes in the synthetic dataset in a controlled manner, giving the possibility of testing new https://ri.conicet.gov.ar/admin/static/img/broom.pngdetection algorithms under more realistic environments.